Análise das cooperativas de saúde da Paraíba com foco na responsabilidade social corporativa - Anjos Júnior, Eufrásio Vieira dos (2015)
Remains growing debate and study the issues of social responsibility within organizations that seek increasingly improve its practices. Against of the scenery with new features and visions of production and consumption, with more demanding and conscious clients, has been cooperative with a different organizational structure and principles of cooperation. The Argentine Institute of Corporate Social Responsibility (IARSE) was created with the mission to promote and disseminate the concept and corporate social responsibility practices and thus promote sustainable development in Argentina. This institute developed the Social Responsibility indicator for Cooperatives (IRSC), in order to include self-management organizations in socially responsible parameters. Seeking an application of ratio analysis of cooperative principles with the principles of corporate social responsibility, the complaint arise the question problem: Health cooperatives from Paraíba have management with a focus on corporate social responsibility, in the other words, they have applied economic, social and environmental values? This paper seeks to identify the existence of Corporate Social Responsibility in the management of health cooperatives from Paraíba. The research was characterized as exploratory based on the method of descriptive research, literature and field research. In terms of the nature of the data, was opted for the qualitative and quantitative approach. The environment of the research were the health branch of the cooperatives in the State of Paraiba, which were registered in SESCOOP -PB. For the comparative analysis of the data was used the statistical test nonparametric Mann -Whitney test (U test), it was adopted the significance level of 5 % (α = 0.05) whose data processing happened with the aid of Statistical Package for Social Sciences - SPSS. From the application of U test can be concluded that Values, Transparency and Governance Cooperative approach cooperatives of Cooperatives Socially Responsible status. In contrast dimensions: Workforce, Environment, Suppliers, Users and Cooperative, Community, Government and Society do not have practices with features that enable the approximation of Socially Responsible status of cooperatives.